Criteria for differentiation of oral and written text in linguistic expertise - Shevchenko, Larysa; Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article is devoted to the dominant characteristics of oral and written text in the aspect of linguoexpertology. The analysis provides a legally defined argumentation for linguistic expertise of oral and written speech, as well as a scientific interpretation of the features of the text in professional research. It is argued that the linguistic expertise of an oral / written text should not be considered only in the context of a forensic examination, in particular authorship or handwriting examination, or a video or audio recording examination. It is emphasized that linguistic examination of oral / written text can be an independent type of linguistic expertise, with appropriately developed criteria and methodological principles for its implementation and testing in judicial practice. The ideas of the article correlate with interdisciplinary approaches, in particular psychological, sociological, medical, etc., which synthesize the criteria of qualitative diagnosis of oral / written text. The authors emphasize modern methods, new discourses and principles of analysis of dominant characteristics of oral / written text in linguoexpert activity. An indicative list of diagnostic questions that are typical for linguistic examinations of oral / written text is offered; the markers for the identification of texts of this type in legal practice are determined. It is proved that the level of evidence in the complex analysis of oral / written texts depends on the depth and accuracy of professional argumentation, typology of linguistic facts proposed for research or their recurrence, as well as the ability to correlate analyzed linguistic units of oral / written text with extralingual factors that led to the appearance of the text.
Keywords: text as verbal consciousness; oral / written text; text characteristics; legal linguistics; linguistic expertise, linguoexpert analysis.